Adoption of Planting Corn Harvesting Cattle Program in North Central Timor Regency - Marsianus Falo; Doppy Roy Nendissa (Journal of Global Innovations in Agricultural Sciences)
The Planting Corn Harvesting Cattle Program (Program Tanam Jagung Panen Sapi - TJPS) is a local government initiative in East Nusa Tenggara Province, North Central Timor Regency, aimed at increasing corn harvest area, production, and productivity to support national food security. This study analyzes the implementation of the TJPS program, key influencing factors, and farmer adoption levels in Insana District. A quantitative descriptive method was used through surveys and structured interviews. The findings show that internal factors such as age, education, farming experience, and external factors like land size and productivity are generally adequate. Respondents had an average age of 49.77 years, 64% with low formal education, and 94% with minimal non-formal education. Farming experience averaged 17.72 years, with 56% managing small farms (<0.65 ha) and 78% having low productivity (1-1.9 tons/ha). The adoption level of TJPS technology is mostly in the early majority category (39.2%), with 15.2% as early adopters and 6.3% as innovators. While the program has been widely adopted, further improvements in farmer participation and technology use are needed . Keywords: Agricultural policy, food security, technology adoption, productivity, sustainability.